A cluster of four cases of meningococcal disease in a single nuclear family. Issue 3 (13th January 2012) - Acheson, P; Barron, R; Borrow, R; Gray, S; Marodi, C; Ramsay, M; Waller, J; Flood, T
Abstract : A cluster of four confirmed cases of meningococcal disease was seen in the same nuclear family across a 15-week period. The cases were three siblings and a parent and all recovered well. The first case was confirmed by meningococcal PCR only but the subsequent three cases were due to indistinguishable strains of serogroup B (B:NT:P1.19-1, 15-11). Contact tracing was initially undertaken and reviewed in detail after each subsequent case. Antibiotic prophylaxis was administered to close family contacts on three separate occasions, including switching of antibiotic agents, with good compliance. Subsequent investigation of the family has not revealed any obvious immunological problem and no further significant infections have been recognised. A cluster of meningococcal disease of this nature and timescale is highly unusual. Details of the cluster, investigation and implications for health protection practice are discussed.